A comprehensive assessment of predictors of fertility outcomes in men with non-obstructive azoospermia undergoing microdissection testicular sperm extraction - Parviz K. Kavoussi; Brady T. West; Shu-Hung Chen; Caitlin Hunn; Melissa S. Gilkey; G. Luke Machen; Keikhosrow M. Kavoussi; Amy Esqueda; J. David Wininger; Shahryar K. Kavoussi (BMC, 2020)
Abstract Background Microdissection testicular sperm extraction (microTESE) in men with non-obstructive azoospermia (NOA) is the procedure that results in the highest number of sperm cells retrieved for in vitro fertilization (IVF). This study presents a novel assessment of predictors of sperm retrieval as well as downstream embryology and pregnancy outcomes in cases of men with NOA undergoing microTESE. Methods A retrospective chart review of 72 men who underwent microTESE for predictors of fertility outcomes including sperm retrieved at microTESE, embryology progression to embryo transfer (ET), clinical pregnancy, live birth, and surplus sperm retrieved for additional IVF/intracytoplasmic injection cycles beyond one initial cycle. Statistical models for each of these outcomes were fitted, with a p-value of < 0.05 considered significant for the parameters estimated in each model. Results Seventy-two men underwent microTESE, and 51/72 (70.8%) had sperm retrieved. Of those, 29/43 (67.4%) reached ET. Of the couples who underwent ET, 21/29 (72.4%) achieved pregnancy and 18/29 (62.1%) resulted in live birth. Of the men with sperm retrieved, 38/51 (74.5%) had surplus sperm cryopreserved beyond the initial IVF cycle. Age, testicular volume, FSH, and testicular histopathology were assessed as predictors for sperm retrieved at microTESE, progression to ET, pregnancy, live birth, and surplus sperm. There were no preoperative predictors of sperm retrieval, clinical pregnancy, or live birth. Age predicted reaching ET, with older men having increased odds. FSH level had a negative relationship with surplus sperm retrieved. Men with hypospermatogenesis histology had higher rates of sperm retrieval, clinical pregnancy, live birth, and having surplus sperm. Conclusions Men who underwent microTESE with a hypospermatogenesis histopathology had better outcomes, including higher rates of sperm retrieval, clinical pregnancy, live birth, and having surplus sperm retrieved. Increasing male partner age increased the odds of reaching ET. No other clinical factors were predictive for the outcomes considered.